Conventional housing schemes: a means of eradicating informal settlements; using City of Mutare as a case study - Chinyamakobvu, Stanley (Midlands State University, 2014)
The Zimbabwean urban areas face several social, economical and environmental problems because of the sprawling urban informal settlements caused by constant housing shortage due to mismatch between high demand for decent accommodation and the supply in urban areas. The ‘Operation Garikai or Hlani kuhle” came after “2005 Operation Clean up or Murambatsvina” has failed to supply urban housing effectively as it is indicated by overcrowding and erection of substandard mushrooming illegal settlements, illegal backyard structures and unauthorised extensions that still remains as a big challenge drawing back local development in cities and towns. The urban Local Authorities however in response is using Conventional Housing Schemes to supply affordable shelter but the sprawling of informal settlements remains rigid. The research from which this report emerged established that from the wake of unprecedented urban informal settlements urban health development decreases. The study then sought to achieve the following objectives; to identify the causes of sprawling urban informal settlements in City of Mutare, to assess problems faced by Mutare urban inhabitants due to the presence of the illegal settlements, to explore the contributions of these Conventional Housing Schemes (C.H.S) in eradicating urban informal settlements ,to identify and analyze the challenges encountered by these schemes in delivering affordable housing to all urban homeless people and to come up with recommendations in addressing effective eradication of informal settlements using these legal housing schemes. The literature reviewed established that there are several causes of illegal settlements including lack of housing caused by inadequate land for settlements development, poor housing policies, bureaucratic laws, vague approvals, deprivation in legal settlements, lack security of tenure in formalised areas and national economic decline. The literature also presented that there are several types of these schemes including Housing co-operatives, Home ownership schemes, pay-for-your service schemes, private sector schemes, donor funded schemes and employer assisted schemes. The researcher employed both qualitative and quantitative research design with the targeted population including council administrative officials, informal settlers, councillors and schemes management officials. The study used non-probability sampling methods such as purposive and systematic sampling techniques. Questionnaires, Interviews and observations were also employed to enrich the study. Data was presented using graphs, pie charts, tables and pictures. Several respondents subscribe to the view that informal settlements are used by inadequate urban housing caused by several challenges faced by the city council and the legal housing schemes including corruption, lack of funds and land for settlement expansion, The researcher recommended thatthe city council should seek more land for housing delivery, increased engagement with financial institutions (banks), involvement of informal settlers in relocation planning, institutional assessment before project implementation, arrest and suspensions perpetrators of land scam ,those involved in corrupt scandals and training and development of schemes management as well as councillors especially those in the housing committee.